Cryptotephras in European Arctic: extending tephrochronology to northern Finland and Russia - Elena Garova 1996- (2020)
Tephrochronology is a powerful method for correlating geological and archeological sequences by utilizing geochemically fingerprinted tephra layers (volcanic ash). Tephra of Icelandic origin is often dispersed to Europe and by studying minor amounts of fine-grained volcanic glass, cryptotephra, it is possible to link and date geological archives located thousands of kilometers away from volcanic source. European Arctic is a key area for understanding postglacial development due to its sensitivity to climate change. It is important to date climate changes precisely and acquire knowledge on their frequency and how rapid they occur. Tephrochronology is the best tool to reach that goal. So far, relatively few studies on (crypto)tephrochronology have been performed, thus the motivation and aim of this project was to improve knowledge on geographical distribution of tephra fall-out and discover cryptotephra layers, which could provide timemarkers to date Holocene environmental evolution in the Arctic. Three peat cores from Kola peninsula, Russia, and one lake core from Finnish Lapland were examined for the presence of cryptotephra. The study revealed cryptotephra deposits from six Icelandic volcanic systems: Hekla, Veiðivötn-Bárðarbunga, Grímsvötn, Öræfajökull, Askja and Katla. Tentative correlations to dated tephra marker-layers are suggested, that indicate the presence of the Glen Garry/A-2000 tephra, CLA-L1 tephra, Öræfajökull 1362 and SILK YN. However, other dating methods such as 14C are needed for a robust correlation. Discovery of at least four basaltic tephras highlights that basaltic shards can travel further than previously thought. This study demonstrates a great potential for tephrochronology in the Arctic.